Study on the relationship between total dissolved solids (TDS) and electrical conductivity (EC) of the aquifers in Ca Mau province - Thu, Trinh Hoai; Huong, Tran Thi Thuy; Trung, Dang Tran (Vietnam Journal of Marine Science and Technology, 2019)
This article has established a set of empirical equations to describe the relationship between bulk resistivity and TDS of the Upper-Middle Pleistocene aquifer (qp2-3) and Lower Pleistocene aquifer (qp1) of the for field survey in 2017 in Ca Mau province. This article has determined the content of TDS based on EC (TDSEC) and established correlation regression equation between TDSLAB and TDS is based on the EC of the qp2-3 aquifer: Y = 0.549X – 0.081 with R2 = 0.975 and Standard Error (SE) = 0.1591. The qp1 aquifer: Y = 0.4669X + 0.0483 with R2 = 0.9869, Standard Error (SE) = 0.0949. Based on these regression correlation equations, we found a high correlation coefficient and small deviation between TDSLAB and TDSEC. Therefore, the determination of TDS content through the EC has reduced the cost of groundwater samples of the aquifers of laboratory analysis in Ca Mau province.